Diversity and equitability of insect pests and natural enemies in brinjal field treated with insecticide (Jahangirnagar University Journal of Biological Sciences, 2016)
Experiment was conducted during winter season to study the diversity and equitability of insect pest species and natural enemies in insecticide treated brinjal fields. Highest number of insect pests were recorded in` Tracer 45 SC, Bactoil (Bt), Nimbicidene 0.03 EC and lowest was in Necstar-50 EC and Proclaim-5 SG treated plots. The highest total abundance of insect pest was recorded in the plots treated with Bactoil and Tracer-45 SC and lowest total abundance was in Helicide (HNPV), Proclaim-5 SG and Booster-10 EC treated plots. The diversity index and equitability of insect pest species were highest in the plots treated with Nimbicidene 0.03 EC and Bactoil in visual search and sweep net methods while Bactoil and Booster 10 EC in pitfall trap method. However, lowest diversity index and equitability were obtained from the plots treated with Booster 10 EC, Proclaim-5 SG, Necstar-50 EC, Tracer-45 SC in visual search and sweep net methods but also in plots treated with Nimbicidene 0.03 EC in pitfall trap method. In case of natural enemies, the highest number of families were recorded in Tracer-45 SC, Nimbicidine 0.03 EC and Bactoil treated plots while lowest was in Helicide, Booster 10 EC, Proclaim-5 SG and Necstar-50 EC treated plots. The highest total abundance of natural enemy was recorded in the plot treated with Bactoil and Tracer-45 SC while lowest abundance was in the plot treated with Necstar-50 EC and Boster-10 EC. The diversity index and equitability of natural enemies were the highest in the plots treated with Proclaim-5 SG, Bactoil, Helicide and Necstar-50 EC in visual search, sweep net method and pitfall trap method while lowest was in Booster 10 EC, Tracer-45 SC treated plots in visual search method, Booster 10 EC and Nimbicidene 0.03 EC treated plots in sweep net method, Necstar-50 EC and Nimbicidene 0.03 EC treated plots in pitfall trap method. Bactoil and Tracer-45 SC were relatively safe for natural enemies and therefore would be fit well into integrated pest management (IPM) against BSFB of brinjal crop.Jahangirnagar University J. Biol. Sci. 4(1): 71-80, 2015 (June)